Understanding the influence of self-concept on clinical decision-making among nurses: A cross-sectional study - Wasan Aboalrob; Ahmad Ayed; Malakeh Z. Malak; Ibrahim Aqtam (PLoS ONE, 2025)
Background Self-concept, defined as an individual’s perception of their professional identity, competencies, and abilities within their nursing role, significantly influences clinical decision-making (CDM) processes. Clinical decision-making represents a complex cognitive process involving critical thinking, problem-solving, and professional judgment that directly impacts patient safety and care quality. Despite established theoretical frameworks linking self-concept to professional performance, limited empirical research has examined this relationship within the unique socio-cultural and healthcare context of Palestine, where nurses face distinctive challenges including resource constraints, high patient acuity, and systemic pressures. This study aimed to examine the influence of self-concept on Palestinian nurses’ clinical decision-making in governmental hospitals. Methods A cross-sectional study was conducted from May to July 2024 in governmental hospitals across Palestine. A total of 381 nurses working in emergency, medical-surgical, and intensive care units participated, selected through convenience sampling. Participants were recruited from 11 governmental hospitals across northern, middle, and southern regions of Palestine to enhance sample diversity. Data were collected using the validated Clinical Decision-Making in Nursing Scale (CDMNS) and the Nurses’ Self-Concept Questionnaire (NSCQ). Cronbach’s alpha coefficients for this study were 0.89 for CDMNS and 0.90 for NSCQ, demonstrating strong internal consistency within the Palestinian nursing context. Results The mean nursing self-concept score was 205.5 ± 26.0 out of 288 (indicating moderately high self-concept, representing 71.4% of the maximum possible score), while the mean CDM score was 152.1 ± 22.2 out of 200 (indicating high decision-making confidence, representing 76.1% of the maximum possible score). A significant positive correlation was found between self-concept and CDM (r = 0.609, p < 0.001). Multiple regression analysis, controlling for age, professional experience, and demographic variables, showed that self-concept was the strongest predictor of CDM (β = 0.641, B = 0.546, p < 0.001), explaining 37.7% of the variance (adjusted R2 = 0.372). Conclusion This study provides empirical evidence that nurses with higher professional self-concept demonstrate significantly stronger clinical decision-making abilities, even after controlling demographic and professional variables. Targeted interventions (e.g., structured mentorship) to enhance self-concept may improve CDM. However, the cross-sectional design limits causal inference, and future longitudinal studies are needed to establish temporal relationships. These findings have important implications for nursing education, professional development, and healthcare policy in Palestine and similar contexts.